Divine disruption : holding on to faith when life breaks your heart - Evans, Tony, 1949-; Hurst, Chrystal Evans; Shirer, Priscilla, 1974-; Evans, Anthony (Musician); Evans, Jonathan, 1981-; Blaine, Jamie (W Publishing Group, an imprint of Thomas Nelson, 2021)
"An insightful Biblical and conversational response from Dr. Tony Evans and his four children-Chrystal Evans Hurst, Priscilla Shirer, Anthony Evans, and Jonathan Evans-on how God uses the hard things of this life to draw us into a deeper faith in Him. Divine Disruption explores the many hardships we experience in life and how God breaks through with the power of hope. In the book, Dr. Tony Evans and his four children-Chrystal Evans Hurst, Priscilla Shirer, Anthony Evans, and Jonathan Evans-discuss their faith-shaking experiences: from the deep grief of losing six loved ones in less than two years' time, with the most devastating blow being the death of Lois Evans, the matriarch of the family, to a deep dive into dealing with the various hard, unexpected things we all face. Life throws many curves-whether the loss of a job or health due to the ongoing worldwide pandemic, or marriage and relationship issues, problems with children, even the recent racial and political unrest. The authors step together into a unique Kingdom Legacy partnership, opening themselves to the honest questions, raw emotions, and solutions they learned to cling to amid their various struggles as they honor their mother's wish to work together. Through their bond and individual strengths, they demonstrate how even the most devastating tragedies can bring glory to God as He continues to meet their needs and build their faith"-- |c Provided by publisher.